Evaluation of the Milk Fatty Acid Profile from Mediterranean Buffalo Cows in the First Eight Weeks of Lactation - Verdurico, Lenita Camargo; Gandra, Jefferson Rodrigues; Júnior, Jose Esler de Freitas; Barletta, Rafael Villela; Venturelli, Beatriz Conte; Mingoti, Rodolfo Daniel; Annibale Vendramini, Thiago Henrique; Rennó, Francisco Palma (Journal of Buffalo Science, 2012)
The aim of this study was to evaluate the fatty acid composition of buffalo milk in the first eight weeks oflactation. It was used 18 cows multiparous Buffaloes of Mediterranean race, the data collection starting four weeksbefore of the calving provided by the 8th week of lactation. The animals were mechanically milked once daily in themorning. The milk samples used for composition analysis were collected weekly from parturition to eight weeks oflactation. There was effect of weeks during the transition period and early lactation for fat yield (kg/day) and for bodyweight of the buffalo cows in lactation (kg).There was effect of weeks of lactation on the fatty acid composition of milkfat.Variations in levels of unsaturated fatty acids of milk fat of buffaloes are similar to those found in dairy cows of thepartum to eighth week of lactation.